An Unusual Prolonged Duration of Illness of Dengue in a Child- A Case Report: An Unusual Prolonged Duration of Illness of Dengue in a Child - Nusrat, Nadia; Paul, Nibedita; Wadia, Nevis (Journal of the Medical College for Women & Hospital, 2025)
Dengue is the most important human virus transmitted by arthropod. It is the leading cause of viral disease that is transmitted by arthropod globally. The virus enters into host through the skin following an infected mosquito bite. The illness progresses as it involves all immune responses including innate, cellular and humoral immunity. When the virus is cleared rapidly from the host, there occurs severe clinical signs of the illness.The term break bone fever has been used to describe the symptom suffered by dengue patients as there is severe joint pain and muscle spasm. There exists a wide range of manifestations clinically for dengue patients including severe dengue (SD) that is dengue shock syndrome (DSS), dengue hemorrhagic fever (DHS) but some patients may show no symptoms that is they remain asymptomatic to dengue fever (DF). Even though most of the cases remain without any symptoms, some patients develop severe form of dengue and may even die. Since specific treatment like antiviral agent or preventive measure such as vaccines for dengue remain undiscovered, the only option is to manage the patients as per symptoms. The infection manifests with broad clinical spectrum, sometimes with unusual manifestation. Here a case is being reported about a boy of 4 years age with unusually prolonged duration of illness, who presented with features of dengue shock (hypotension, narrow pulse pressure and prolonged Capillary Refill Time). J Med Coll Women Hosp.2025; 21 (2):144-149